A filosofia jurídico-pragmática como fundamento para uma teoria do precedente judicial - Ferreira , Cicero Alberto Mendes (2017)
The present work has the scope to analyse, from a pragmatist perspective, the Judicial Precedent Theory, so as to consider, in the face of the systematic observation of judicial precedents inserted in the brazilian legal-positive arrangement by the new Code of Civil Procedure, about the inferential structure that is capable of establishing the determinant foundations – ratio decidendi – of a juridical decision capable of distinguishing the hermeneutical parameter to be taken as a starting point in similar cases later submitted to the appreciation of the Judiciary, in this desideratum using the abductive inference of Charles Sanders Peirce. Peirce's pragmatism, manipulated by abduction, is taken as a method of apprehending law under an anti-essentialist, anti-foundationalist prism and marked by the contextualisation of the interpretive activity and even of the Theory of Knowledge, so that the practical consequences of concepts, the appreciable verifiable effects of the use of an idea in the face of the need to present plausible solutions to real problems have a relevant relevance in the juridical knowledge, characterizing the activity of the interpreter aiming at the attribution of meaning to the law in an eminent creative context. Thus, the manifestation in the jurisdictional provision aiming at the establishment of the judicial precedent, considered from the pragmatist philosophical framework, would be characterized by an inference of the consequences for the causes, promoting the integration between the contexts of discovery and Justifying and understanding the construction of knowledge as a result of a creative insight of the subject, logically implemented through abductive reasoning conceived in the context of discovery and justified posteriorly – which does not indicate a chronological precedence between the context of the discovery and the context of the justification, but rather logic, even though the manifestations in such contexts are understood as non-existent expressions within the scope of the Theory of Knowledge. In this sense, the precedent is identified in addition to the conception of parametrization of the Judiciary's performance with support in rationality and aiming for a conceptual certainty standard based on the idea of stability and coherence, identified as an instrument for the achievement of a rational correction model, on the contrary, by describing knowledge about law as a fallible expression, based on the assumption of credible hypotheses through abduction, the observation of the judicial precedent represents a practical requirement of predictability of the Judiciary, without departing from Inexorable commitment to the adequacy of the concepts to the consolidated social objectives, and it is also essential to undertake repeated tests of fallibility of the said conceptual hypotheses to the socio-political paradigm, even aiming at the permanent improvement of science itself in an open society. plural and democratic.